Scabies in Infants: Series of 51 Cases - Isabel Betlloch-Mas; Elena Boluda-Verdú; Noelia Jara-Rico; Verónica Sánchez-García; Laura Berbegal-De Gracia; Eusebi Chiner-Vives (MDPI AG, 2024)
We conducted a two-year retrospective evaluation of infants aged under two years with a confirmed, clinical, or suspected diagnosis of scabies in a healthcare center in Alicante (Spain) to determine possible factors associated with diagnostic delay and poor treatment response. We collected epidemiological, clinical, diagnostic, and treatment variables. After describing our findings as mean values and percentages, we compared categorical variables using the Student's t-test and the Mann-Whitney U test, and we compared continuous variables with the Chi2 test and Pearson's correlation coefficient. We included 51 infants (19 boys and 32 girls) with a mean age of 15 months. The main source of contagion was the family; half of the infants lived with four or more people. According to the International Consensus Criteria for the Diagnosis of Scabies, confirmed scabies was diagnosed in 45% of cases and clinical scabies in 47%, and 45% of cases had a diagnostic delay. Lesions mainly affected the hands, feet, and trunk, with papules in 92% of cases and burrows in 55%. The predominant symptoms were pruritus (94%) and irritability (69%). Regarding treatment, 98% of the infants received topical permethrin and 35% received oral ivermectin. Treatment failed in 76% of infants. Living in large family units was associated with a higher risk of contagion and therapeutic failure. Diagnostic delay was associated with previous misdiagnosis.